Repetitive transcranial magnetic stimulation over the posterior parietal cortex improves functional recovery in nonresponsive patients: A crossover, randomized, double-blind, sham-controlled study - Xu, Chengwei; Wu, Wanchun; Zheng, Xiaochun; Liang, Qimei; Huang, Xiyan; Zhong, Haili; Xiao, Qiuyi; Lan, Yue; Bai, Yang; Xie, Qiuyou (Frontiers in Neurology, 2023)
Background Recent studies have shown that patients with disorders of consciousness (DoC) can benefit from repetitive transcranial magnetic stimulation (rTMS) therapy. The posterior parietal cortex (PPC) is becoming increasingly important in neuroscience research and clinical treatment for DoC as it plays a crucial role in the formation of human consciousness. However, the effect of rTMS on the PPC in improving consciousness recovery remains to be studied. Method We conducted a crossover, randomized, double-blind, sham-controlled clinical study to assess the efficacy and safety of 10 Hz rTMS over the left PPC in unresponsive patients. Twenty patients with unresponsive wakefulness syndrome were recruited. The participants were randomly divided into two groups: one group received active rTMS treatment for 10 consecutive days (n = 10) and the other group received sham treatment for the same period (n = 10). After a 10-day washout period, the groups crossed over and received the opposite treatment. The rTMS protocol involved the delivery of 2000 pulses/day at a frequency of 10 Hz, targeting the left PPC (P3 electrode sites) at 90% of the resting motor threshold. The primary outcome measure was the JFK Coma Recovery Scele-Revised (CRS-R), and evaluations were conducted blindly. EEG power spectrum assessments were also conducted simultaneously before and after each stage of the intervention. Result rTMS-active treatment resulted in a significant improvement in the CRS-R total score (F = 8.443, p = 0.009) and the relative alpha power (F = 11.166, p = 0.004) compared to sham treatment. Furthermore, 8 out of 20 patients classified as rTMS responders showed improvement and evolved to a minimally conscious state (MCS) as a result of active rTMS. The relative alpha power also significantly improved in responders (F = 26.372, p = 0.002) but not in non-responders (F = 0.704, p = 0.421). No adverse effects related to rTMS were reported in the study. Conclusions This study suggests that 10 Hz rTMS over the left PPC can significantly improve functional recovery in unresponsive patients with DoC, with no reported side effects. Clinical trial registration www.ClinicalTrials.gov, identifier: NCT05187000.